Peripheral Neutrophils-Derived Matrix Metallopeptidase-9 Induces Postoperative Cognitive Dysfunction in Aged Mice - Huang, Lili; Tian, Weitian; Chen, Xuemei; Xu, Huan; Dai, Wanbing; Zhang, Yizhe; Wu, Xiaodan; Yu, Weifeng; Tian, Jie; Su, Diansan (Frontiers in Aging Neuroscience, 2022)
Background Aging is one of the most important risk factors of postoperative cognitive dysfunction (POCD); however, the mechanisms are still not completely understood. In this study, we explore the roles of matrix metalloproteinase-9 (MMP-9) in aged mice with POCD. Methods Appendectomy was performed in 18-month-old C57BL/6 and MMP-9–/– mice under anesthesia to establish the POCD model. Learning and memory were assessed using the Morris water maze (MWM) or Barnes maze. Protein expression of MMP-9 was measured by Western blotting or enzyme-linked immunosorbent assay (ELISA). To explore the role of neutrophils-derived MMP-9 in POCD, we treated mice with anti-Gr-1 monoclonal antibody to deplete peripheral neutrophils. And the percentage of neutrophils and other leukocytes were detected by flow cytometry. We further used sodium fluorescein (NaFlu) to evaluate the blood–brain barrier (BBB) permeability. Results The spatial learning and memory ability was injured, and expression of MMP-9 increased in both plasma and the hippocampus after anesthesia/surgery. However, cognitive dysfunction was alleviated in both MMP-9–/– and peripheral neutrophils-depleted mice. The permeability of BBB was increased after anesthesia/surgery while recused by anti-Gr-1 antibody administration. Conclusion These findings suggest that peripheral neutrophils-derived MMP-9 could lead to POCD of aged mice through increasing the BBB permeability.